A Team-Based Strategy in Bachelor’s Studies of Lithuanian university: Exploring the Possibilities of Adaptation - Aleksandravičiūtė, Birutė; Liekis, Kęstutis (Pedagogika, 2020)
Team-based learning strategy is widely applied in the world’s higher education institutions in the most diverse fields of studies. Its popularity is due to its positive impact on student’s achievement. Team-based learning increases student’s motivation and involvement into the study process, and its implementation enables students to acquire the competencies necessary in the modern labor market. The research problem: what are the opportunities to adapt team-based learning strategies into university studies? Research object: team-based learning strategy. Aim: to explore the possibilities of Team-based learning strategy in bachelor studies. The research found, that in order to successfully adapt this strategy, it should be taken into consideration that a significant part of students is working students, and classes are missed. In cases where attendance is not compulsory, larger teams should be formed. It has been found that it is difficult for students to apply theoretical knowledges by solving real practical situations, so the teachers must to be prepared various of practical examples, in order to successfully adapt the team-based learning strategy, it is expedient to use already available, high-quality studies materials and properly adjust schedules.